Analysis Slope Stability Using RMR and SMR Method in Nupaomba Area Tanantovea Donggala - Uno, Djamal Adi Nugroho; Uno, Irianto; Saputra, Apriadi; Arum, Deno Ambar; Mumin, Riqa Permatasyara; Alfaed, Moh Rizky Fadel (Jambura Geoscience Review, 2025)
Landslide disasters frequently occur in the Nupabomba area due to its steep slopes and its role as a primary access road for the local community. This study aims to analyze slope stability using the Rock Mass Rating (RMR) and Slope Mass Rating (SMR) methods to assess the potential for landslides. The research was conducted at coordinates (Universal Transverse Mercator) UTM 829117.90 – 831853.89 mE and 9920980.82 – 9920308.34 mS. Data collection involved field measurements using the scanline method, focusing on discontinuities, lithology, and rock strength. The results indicate that at Station 01, the slope consists of slate rock with an RQD value of 70% and UCS of 23 MPa. The calculated RMR value is 58, placing it into Class III (fair rock), with an SMR value of 55.4, indicating partially stable conditions. Meanwhile, at Station 02, the slope consists of phyllite rock with an RQD value of 70% and UCS of 52 MPa. The RMR value is 62, classifying it as Class II (good rock), and the SMR value is 61.6, indicating a stable condition. These findings provide crucial insights into the geotechnical characteristics of the area, which are essential for landslide risk mitigation and infrastructure planning. The study highlights the need for continuous monitoring and possible reinforcement strategies, particularly in areas categorized as partially stable. Further research incorporating geotechnical modeling and additional stability analysis is recommended to enhance slope stability predictions and inform mitigation strategies.